Demographic and prognostic landscape of upper urinary tract urothelial carcinoma: an analysis of a national cancer database - Hsia, Beau; Moroz, Mark; Sipes, Ethan; Chang, Amber; Jundi, Rania; Rafie, Susan; Silberstein, Peter; Tauseef, Abubakar (Frontiers in Urology, 2026)
PurposeUpper urinary tract urothelial carcinoma (UTUC) is an uncommon malignancy of the urogenital tract with a wide range of clinical outcomes. While prognostic factors for bladder-based UC are established, less is known about tumors in other locations and the impact of socioeconomic disparities. This study uses a large national database to identify key demographic, clinical, and socioeconomic predictors of overall survival in UC patients, focusing on the primary tumor site.MethodsWe conducted a retrospective analysis of 12,300 patients diagnosed with UC of the kidney and renal pelvis between 2004 and 2020 from the National Cancer Database (NCDB). Multivariable Cox proportional hazards regression was used to analyze the association between overall survival and factors including patient demographics, tumor characteristics, primary tumor site, and socioeconomic status.ResultsThe cohort was predominantly male (59%) and White (91%), with a mean age of 71 at diagnosis. Multivariable analysis identified several factors significantly associated with survival. Renal pelvis tumors, the most common primary site (84.9%), were associated with significantly improved survival (HR = 0.84; 95% CI: 0.8–0.9; p<0.001). Compared to males, females exhibited a 15% lower hazard of death (HR = 0.85; 95% CI: 0.81-0.90; p<0.001). Factors associated with worse survival included a higher Charlson-Deyo comorbidity score (HR = 1.51; 95% CI: 1.39-1.65; p<0.001) and advanced NCDB tumor stage. Socioeconomically, patients with higher income (HR = 0.82; 95% CI: 0.75-0.90; p<0.001) and private insurance or Medicare (HR = 0.70; 95% CI: 0.57-0.87; p<0.001) had improved survival. Adjuvant chemotherapy was associated with a lower hazard of death (HR = 0.84; 95% CI: 0.75-0.95; p=0.007), whereas primary radiation therapy was associated with a higher hazard of death (HR = 1.69; 95% CI: 1.54-1.86; p<0.001).ConclusionThis large-scale analysis identifies the primary tumor site as a key prognostic factor in UC, with renal pelvis tumors demonstrating more favorable survival. The study also confirms the significant influence of comorbidity and tumor stage while uniquely highlighting that socioeconomic factors, such as income and insurance, are powerful predictors of outcome. These findings underscore the need for optimized, site-specific treatment strategies and concerted efforts to address healthcare inequities in the management of upper tract UC.